KEABSAHAN AKTA PERJANJIAN PENGIKATAN JUAL BELI, SURAT KUASA MENJUAL DAN/ATAU MELEPAS HAK ATAS OBJEK YANG MENJADI AGUNAN DI BANK - Saputro, Agus Purwo; Huda, Miftakhul (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
This research aims to determine the reasons for the invalidity of deeds of sale and purchase agreements, power of attorney for sale and purchase, and/or release of rights to objects mortgaged to banks, as well as the legal consequences of this invalidity. The research methode used is normative juridical, where theoretical aspects are analyzed and interpreted. Secondary data originating from primary and secondary legal sources is the basis for research. Primary legal sources include authoritative legal documents, while secondary legal sources include publications about law such as books, texts, legal journals, and comments on court decisions. then processed and studied using qualitative descriptive methods. The research results show that the causes of the invalidity of the deed can be explained by several factors. First, a power of attorney to sell does not have executory power to settle debts, and the absolute prohibition on the use of power is particularly important in the context of property sales. Second, the principle that the granting of power of attorney must be in line with the rights of the person giving the power of attorney is very important in determining the validity of these documents. The Sales and Purchase Agreement (PPJB) also plays an important role in ensuring there is a clear understanding of the rights and obligations in the legal relationship between the seller and the buyer. The notary as the official in charge of making deeds must ensure that the legal documents he makes comply with the provisions of the laws and regulations. Non-compliance can result in losses for all parties involved, especially in terms of rights protection and legal certainty.